The Implementation of the AISAS Model on “Bar Biiru - Not a Sushi Bar” on Instagram - Janitra, Ogya Adwidtiya; Aryohadi, Miftah Tri; Wirasari, Ira (Gorga : Jurnal Seni Rupa, 2025)
Advertising is one of the many elements of promotion activity, which also includes paid sponsorship. With the advancements in internet technology in Indonesia, advertisement through digital media has become a significant opportunity for business owners to showcase their products or services to a global audience without geographical limitations. This study aims to explore the process of creating advertising content by Bar-Biiru – Not A Sushi Bar on Instagram using the AISAS model (Attention, Interest, Search, Action, Share). The research methods employed include literature review and visual data processing to gain insights from the content of Biiru – Not A Sushi Bar in digital media. The findings demonstrate that advertising through social media facilitates the delivery of authentic brand experiences, supported by collaborations with content creators as a form of digital word-of-mouth marketing. This study provides valuable insights into the significance of engaging visuals, accessible information, and strategies to enhance brand awareness through effective digital interactions. Additionally, it is anticipated to serve as a reference for developing digital promotional strategies for other businesses. The evolution of technology continues to shape the landscape of advertising, leading to the emergence of novel methods and media platforms, particularly through social media.